Bisphosphonate use in Duchenne Muscular Dystrophy – why, when to start and when to stop?. (2nd April 2016) - Wood, Claire L.; Marini Bettolo, Chiara; Bushby, Kate; Straub, Volker; Rawlings, David; Sarkozy, Anna; Owen, Catherine; Cheetham, Timothy D.
ABSTRACT: Introduction : Long term use of glucocorticoids has dramatically improved the disease course in Duchenne Muscular Dystrophy (DMD) and patients are now frequently surviving into their thirties. However, there are significant side-effects associated with chronic glucocorticoid administration, including a reduction in bone mineral content. The resultant osteoporosis, which predisposes to fragility fractures of both long bones and vertebrae, is a major cause for concern. There is a wide variation in clinical practice regarding the use of bisphosphonates (BP) as a means of preserving skeletal integrity in this patient group. Areas covered : This review describes the rationale and evidence for use of BP in DMD, and discusses the main side-effects and limitations of their use. It will introduce the controversial concept of a bisphosphonate holiday (a break in BP therapy after a prolonged period of use) and then summarise the potential strategies for monitoring bone health when BP is stopped. It will highlight evidence from adult studies and discuss the paucity of knowledge relating to the growing skeleton. Expert Opinion : Bisphosphonates are currently the most effective therapy for steroid-induced osteoporosis in DMD but the side-effects and consequences of their long term use remain a concern. The impact of a BP holiday on the developing skeleton is unknown and further controlled studies in children are required.